Biochemical Profiling of Saliva and Gingival Crevicular Fluid in Peri-Implant Mucositis: A Focus on Bone Metabolism, Oxidative Stress, and Matrix Remodeling: Biochemical Profiling of Peri-Implant Fluids - Wan, Huiqian; Wang, Ying (Journal of Medical Biochemistry, 2026)
Background: Peri-implant mucositis involves coordinated disturbances in bone metabolism, oxidative stress, and matrix remodeling, but these pathways are rarely assessed jointly in saliva and gingival crevicular fluid (GCF). This study aimed to establish a quantitative biomarker profile in peri-implant health and peri-implant mucositis and to compare the detection value of the two fluids.Methods: This single-center retrospective study included 64 patients with peri-implant health and 71 patients with peri-implant mucositis who were enrolled between August 2024 and December 2025. Saliva and GCF samples were collected. Basic biochemical parameters were measured using an automated biochemical analyzer. More than 30 biochemical biomarkers, including OCN, CTX-I, MDA, 8-OHdG, MMP-8, MMP-9, MPO, and NE, were quantitatively assessed using double-antibody sandwich enzyme-linked immunosorbent assay (ELISA), competitive ELISA, colorimetric assays, and fluorogenic substrate assays. Laboratory quality control was applied throughout sample testing.Results: Compared with saliva, GCF showed more pronounced biomarker alterations in the mucositis group, with most GCF biomarker changes being approximately 1.5- to 3.0-fold greater than the corresponding salivary changes; MPO and NE increased by more than 2.5-fold, suggesting that GCF more sensitively reflected local microenvironmental disruption. Markers of bone metabolism indicated a negative balance, with decreased bone formation markers, including osteocalcin (OCN), bone-specific alkaline phosphatase (BALP), and N-terminal propeptide of type I procollagen (PINP), and increased bone resorption markers, including C-terminal telopeptide of type I collagen (CTX-I), tartrate-resistant acid phosphatase 5b (TRAP-5b), and cathepsin K (CTSK) (P
Keywords: Peri-implant mucositis; Gingival crevicular fluid; Saliva; Clinical biochemistry; Bone metabolism; Oxidative stress; Matrix remodeling